Effect of Ag on interfacial segregation in Mg–Gd–Y–(Ag)–Zr alloy. (15th August 2015) - Zhou, H.; Cheng, G.M.; Ma, X.L.; Xu, W.Z.; Mathaudhu, S.N.; Wang, Q.D.; Zhu, Y.T.
Abstract: Interfaces such as twin boundaries, stacking faults and grain boundaries often play an important role in controlling mechanical properties of metals through interaction with dislocations. Segregation of alloy elements and impurities to these interfaces can stabilize them and produce a large strengthening effect. Here we report the effect of Ag on segregation of alloy elements at twin boundaries, stacking faults and grain boundaries in the Mg–Gd system. Specifically, for the first time a spinal-shaped periodic segregation is observed at the {1 0  1 ¯  2} twin boundary and high-angle lamellar grain boundary in the Mg–Gd–Y–Zr alloy due to the presence of the Ag addition. The segregation consists of Gd- and Ag-rich columns. It appears that high Ag content in the spinal-shaped segregation induces fcc-like cell structures.